(untitled) (Journal of actual problems of jurisprudence, 2018)
In Kazakhstan, the land fund more involved in the commodity and the economy. Enhanced anthropogenic, man-made pressures on land resources. A rare kind of human activity is not possible – without affecting the land or land use as a spatial basis or means of production. Therefore, protection of land in these conditions, is an organization of business and other land-related activity, which does not have the negative anthropogenic impact on the land. That is, the protection of land expresses the system requirements for the implementation of various land-related activities. Key words: Land, land conservation, environment, mineral resources, conservation lands.